PENGARUH PELAPORAN TERINTEGRASI DAN PENGUNGKAPAN RISIKO TEKSTUAL TERHADAP NILAI PASAR - Herlina Pusparini; Nurabiah Nurabiah; Yusli Mariadi (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
This study aims to determine whether integrated reporting has a positive impact and whether textual risk disclosure (TRD) negatively impacts the company's market value. Signaling theory is used in this study, which focuses on how integrated reporting and TRD provide positive signals to investors so that they can increase firm value. Purposive sampling was used when the samples were mining companies listed on the Indonesia Stock Exchange (IDX). There are 168 observations and 56 firms in the sample. Stata 14.2 is used to analyze and multiple regression to test the hypothesis. As a result, integrated reports and Textual Risk Disclosures (TRD) do not affect the company's market value. This research has implications for stakeholder policies where other factors such as financial performance, industry stability, and other macroeconomics are more dominant in influencing company value. Companies can consider increasing the quality and relevance of their risk disclosures to provide more helpful information for investors.